- USAHA KESEJAHTERAAN ANAK JALANAN SELAMA PANDEMI COVID-19 OLEH SAHABAT ANAK GROGOL: - - Siti Dzilla Rahmadya; Hj. Wahyuni Retnowulandari (Fakultas Hukum Universitas Trisakti, 2023)
The very high number of street children at present, which are spread across the five municipalities of the Special Capital Region of Jakarta, brings these children into the various risks they face. In this research, it focuses on child welfare efforts for street children during the Covid-19 pandemic by having two problem formulations, namely (1) Is the welfare business organized by Sahabat Anak Grogol in fulfilling the welfare of street children in accordance with relevant laws and regulations, (2) What facilities and services are provided by Sahabat Anak Grogol during the Covid-19 Pandemic so that the welfare of street children continues to be fulfilled. This research method uses normative law supported by data with empirical data and the nature of the research used in this research is descriptive-analytical and conclusions are drawn by deductive method. The conclusions obtained in this study are the fact that the role of street children's parents is one of the important things or factors that need to be considered in the success of welfare efforts carried out for street children, besides that there is still a lack of involvement of the Regional Government in helping fulfill welfare efforts organized by the community for street children.